Analysis of image quality of pediatric chest radiography in the neonatal intensive care unit (NICU) of Hospital Universiti Sains Malaysia (HUSM) - Awal, Mohd Firdaus Mohd (2023)
Abstract Background: Chest radiography is the commonest radiography examination performed in the radiology department. It is vital to ensure the excellent quality of the chest radiograph performed to aid in diagnosing the clinical condition and to reduce the incidence of the repeated chest radiograph. One of the methods to analyse the quality of the chest radiograph is using a visual grading analysis score (VGAS) scoring. Other factors that affect the quality of the radiograph are image collimation by using collimation score and body weight. This study aims to analyse the quality of the chest radiographic performed in our centre's neonatal intensive care unit (NICU) using a visual grading analysis score VGAS scoring. We also will study the correlation between VGAS score, collimation score, body weight and gender. Methods: This cross-sectional study was done at NICU Hospital University Sains Malaysia, Kubang Kerian, Kelantan. A portable chest radiograph performed in the neonatal intensive care unit NICU during the study duration was reviewed and scored according to the VGAS scoring criteria and collimation score. The correlation between VGAS score, collimation score, body weight and age were tested using the Pearson correlation test. Correlation between VGAS score between males and females were tested using One-way ANOVA. Results: The mean VGAS score and collimation score were 21.66 ± 1.54 and 2.57 ± 1.96 respectively. There is significant weak negative correlation between the collimation score and VGAS score (r = -0.182, p = 0.010). There is also a significant weak negative correlation between age and VGAS score (r = -0.303, p < 0.001). However, there was no significant correlation found between weight and VGAS score (r = 0.035, p = 0.630) and no significant difference in VGAS score between males and females (F(1,195) = 0.669, p = 0.414). Conclusion: VGAS scoring for our center shows the excellent quality of chest radiographs. There are statistically significant correlation between VGA score with the collimation score and patient’s age.